Assessing climatic, travel, and methodological influences on whole-match and worst-case scenario locomotor demands of international men`s rugby sevens match-play - Ullersperger, E.; Hills, S. P.; Russell, M.; Waldron, M.; Shearer, D.; Lonergan, B.; Farrow, T.; Eager, R.; Kilduff, L. P. (European Journal of Sport Science, 2023)
This study assessed the influence of environmental factors, air travel, and epoch estimation method on locomotor demands of international men`s rugby sevens match-play. Eighteen men`s rugby sevens players wore 10 Hz Global Positioning Systems (STATsport) during 52 international matches over nine global tournaments (418 observations). Whole-match average speed was recorded, whilst average speed and relative high-speed distance (>5.0 m·s-1) were quantified using FIXED and ROLL methods over 60-420 s epochs (60 s increments) to establish worst-case scenario demands. Linear mixed models compared FIXED versus ROLL estimation methods and assessed whether temperature, humidity, travel duration, number of time-zones crossed, and travel direction were associated with locomotor responses. Temperature and humidity were positively associated with overall and worst-case scenario average speed (effect estimates; b: 0.18-0.54), whilst worst-case scenario high-speed distance at 300 s was also related to temperature (b: 0.19). Easterly air travel compromised overall and 180 and 300 s worst-case scenario average speed (b: -8.31 to-7.39), alongside high-speed distance over 300 s (b: -4.54). For worst-case scenario average speed and high-speed distance, FIXED underestimated ROLL at all epoch lengths (~9.9-18.4%, p=0.001). This study indicated that international rugby sevens match-play locomotor responses were greater as air temperature increased but reduced following eastward air travel. Underestimation of demands in FIXED vs ROLL over 60-420 s epochs was confirmed. Such climatic and travel influences warrant the adoption of strategies targeted at maximising performance and safety according to the tournament conditions. Knowing the most demanding periods of match-play facilitates training specificity.